Law Reform in Parliamentary Democratization: A Comparative Study of Legislative Terms in Indonesia, Philippines, and the United States of America - Muhammad Mutawalli Mukhlis; Hariyanto Hariyanto; Maskun Maskun; Muhammad Saleh Tajuddin; Andi Tenri Yeyeng (Journal of Law and Legal Reform, 2025)
The purpose of this study is to compare the taxation policies of legislative members’ terms of office in Indonesia with the Philippines and the United States, along with an analysis of the urgency of the legislative member’s term of office. The study methodology employed is normative legal research. The findings of the research show that the legislative member’s term of office has not been regulated in the Indonesian constitution because Law No. 17 of 2014 only regulates the length of office in one period. This is distinct to the Philippines, which establishes a term limit for legislative members, where the term of office of senate members is 6 years and may be re-elected twice, while the term of office for the House of Representatives is 3 years and can be re-elected in three terms. Meanwhile, in the United States, there is also no regulation regarding the taking of terms of office, only the term of office of legislative members in the United States is only 2 (two) years each period, while in Indonesia it is quite long, namely 5 (five) years.